Pengaruh Gaya Pengepresan terhadap Perubahan Suhu Badan pada Pembuatan Tablet Effervescent Buah Markisa - Ansar Ansar; Budi Rahardjo; Zuheid Noor; Suyitno Suyitno (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
Research about effect of compression force on material temperature change in the markisa fruit effervescent tablet has not been properly. So that the objectives of the research are (1) to the develop a mathematical models to predict change of material temperature and (2) to study variables influences to material temperatures during compression. The investigation was done by varying six variables are the high of material in punch, punch diameter, particles diameter, moisture contents, compress force, and test speed. The result of the research showed that change of material temperature during compression can be predict with mathematical equation of dimension analysis. To prove whether the sixth independent variables influence to dependent variable together, with used analysis of variants and the research showed that the F value (35.33) is greater than the F table (2.51). This indicated that the sixth independent variables more influences to change of material temperature during compression.